Nomenclator botanicus of Fagaceae in Latin America - Bartholomew, Bruce; Almeda, Frank (Phytotaxa, 2023)
Latin America is one of the centers of Fagaceae distribution, at least for the genus Quercus. There are a total of 145 Fagaceae species native to Latin America of which 143 are Quercus, with the other two being one species of Fagus and one species of Trigonobalanus. Within Quercus, 32 species that occur in Latin America extend into the United States of America and one, Q. muehlenbergii, ranges as far north as Canada. By far the main center for Quercus in Latin America is Mexico (137 species of which 83 are endemic). The number of species rapidly falls off in Central America, and only one species (Q. humboldtii) occurs in South America (Colombia). In this nomenclator we include one new name (nom. nov.) for a recognized species that was a later homonym when published. We also lectotypify 171 names, and neotypify one species.